Anais Do I Workshop De Aplicações Práticas De Learning Analytics Em Instituições De Ensino No Brasil (WAPLA 2022) 2022
DOI: 10.5753/wapla.2022.226423
|View full text |Cite
|
Sign up to set email alerts
|

Análise do Nível de Maturidade na Adoção de Learning Analytics em Instituições de Ensino Superior Brasileiras

Abstract: A adoção de Learning Analytics (LA) em Instituições de Ensino Superior (IES) é considerada uma tarefa desafiadora, por sugerir mudanças na estrutura da IES e abranger atividades em diversos setores do sistema de ensino. Compreender o nível de maturidade dos projetos de LA existentes dentro das IES torna-se fundamental para que as instituições consigam ampliar seus projetos e abranger todos os seus setores. Este trabalho apresenta um estudo exploratório sobre o nível de maturidade da LA nas IES das regiões do s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Here, even though all participants agreed on the potential of LA to improve learning and personalized processes, they mentioned the need for simple and powerful visualizations, and suggestions of pedagogical actions by the LA tool as requirements for the adoption of LA solutions, and the risk of invading students privacy as one of their main concerns. Continuing within the context of Brazil, an initial survey carried out by [35] in the south and southeast regions with Higher Education Institutions (HEIs) revealed that only half of the participant institutions have implemented some form of Learning Analytics (LA) solution. Moreover, merely 6% of them employed these solutions systematically.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, even though all participants agreed on the potential of LA to improve learning and personalized processes, they mentioned the need for simple and powerful visualizations, and suggestions of pedagogical actions by the LA tool as requirements for the adoption of LA solutions, and the risk of invading students privacy as one of their main concerns. Continuing within the context of Brazil, an initial survey carried out by [35] in the south and southeast regions with Higher Education Institutions (HEIs) revealed that only half of the participant institutions have implemented some form of Learning Analytics (LA) solution. Moreover, merely 6% of them employed these solutions systematically.…”
Section: Related Workmentioning
confidence: 99%
“…According to [14], the implementation of ICT in education in Brazil faces several barriers, such as i) lack of government investment, ii) insufficient digital literacy of teachers, iii) scarcity of human resources trained in handling technologies, and iv) disparities between public and private education. [16] pointed out that, even with large amounts of data collected about students' digital traces, most of the LA solutions implemented in Higher Education Institutions in Brazil still are of small scale. Taking into account the scarcity of empirical studies that examine the practical and real possibilities of using LA [17], this investigation intends to better understanding this aspect from the perspective of LA developer in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Uma vez que a menor granularidade se refere ao desempenho dos estudantes em disciplinas, não há necessidade do uso de um pipeline de dados real-time, sendo o processo de ETL executado em lote para carregar os data marts pelo menos uma vez por semestre. As principais etapas da elaborac ¸ão da plataforma de BI são: A plataforma foi estruturada de forma a dar suporte ao processo de adoc ¸ão de AA e LA [Scheneider et al 2022]. Portanto, ela foi desenvolvida em alinhamento com demandas de diferentes setores da IES interessados na gestão acadêmica.…”
Section: Métodounclassified